2016
DOI: 10.1093/brain/aww095
|View full text |Cite
|
Sign up to set email alerts
|

Estimating changing contexts in schizophrenia

Abstract: SEE STEPHAN ET AL DOI101093/AWW120 FOR A SCIENTIFIC COMMENTARY ON THIS WORK: Real world information is often abstract, dynamic and imprecise. Deciding if changes represent random fluctuations, or alterations in underlying contexts involve challenging probability estimations. Dysfunction may contribute to erroneous beliefs, such as delusions. Here we examined brain function during inferences about context change from noisy information. We examined cortical-subcortical circuitry engaging anterior and dorsolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…The current results additionally provide preliminary support for the idea that a reduced ability to adaptively update expectations in PSZ could be related to decreased coupling between regions that signal and utilize the RPE to update behavior; the strength of learning rate modulation-dependent dmPFC-VS connectivity was decreased in PSZ, and especially so in PSZ with more severe motivational deficits. This finding echoes those of Kaplan et al (2016) who observed changes in ACC effective connectivity within a change-detection network. In that study, increased PFCmidbrain effective connectivity tracked with delusional severity, whereas we observed decreased dmPFC-VS connectivity as a function of motivational deficit severity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current results additionally provide preliminary support for the idea that a reduced ability to adaptively update expectations in PSZ could be related to decreased coupling between regions that signal and utilize the RPE to update behavior; the strength of learning rate modulation-dependent dmPFC-VS connectivity was decreased in PSZ, and especially so in PSZ with more severe motivational deficits. This finding echoes those of Kaplan et al (2016) who observed changes in ACC effective connectivity within a change-detection network. In that study, increased PFCmidbrain effective connectivity tracked with delusional severity, whereas we observed decreased dmPFC-VS connectivity as a function of motivational deficit severity.…”
Section: Discussionsupporting
confidence: 88%
“…In both studies, these impairments scaled with the severity of motivational deficits. Multiple other groups have reported abnormal prefrontal activity (or fronto-parietal connectivity) in association with belief updating in uncertain environments (Kaplan et al, 2016;Koch et al, 2010;Paulus, Frank, Brown, & Braff, 2003). While these findings suggest that abnormalities in learning rate modulation may contribute to RL deficits in PSZ, even when RPE signals are intact, no systematic investigation of dynamic learning rate modulation has been conducted in this population.…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, DCM studies of schizophrenia have started to appear (Allen et al, 2010, Bastos-Leite et al, 2015, Benetti et al, 2009, Brodersen et al, 2014, Curcic-Blake et al, 2015, Dauvermann et al, 2013, Dima et al, 2012, Kaplan et al, 2016, Schmidt et al, 2014). Almost invariably, these studies disclose abnormal effective connectivity involving the prefrontal cortex.…”
Section: The Physiology Of Dysconnectionmentioning
confidence: 99%
“…Some DCM studies have looked explicitly for the synaptic correlates of precision. For example, “in processing subsequent information indicating reduced uncertainty of their predictions, patients engaged relatively increased mid-brain activation, driven in part by increased dorsolateral prefrontal cortex to midbrain connectivity” (Kaplan et al, 2016). …”
Section: The Physiology Of Dysconnectionmentioning
confidence: 99%
“…We used Dynamic Causal Modeling, DCM (Friston et al, 2003) as implemented in SPM12 (DCM10) to examine how cortical and subcortical brain regions interacted during TC-related tasks in Experiments 1 and 2. Time series during TC were extracted from each of 6 regions-of-interest (ROI) in the IPS, AG, FFG, IFG, DLPFC and Str for each individual at a peak within 10mm of the group-level activation peak (at p<0.05 whole brain FWE corrected) and with p<0.05 at the individual subject level, as before (Kaplan C.M. et al, 2016).…”
Section: Random-effects Analyses At the Second (Group) Level In Expermentioning
confidence: 99%